PEMBERDAYAAN TUTOR SEBAYA DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH - Lukmanulhakim, Cecep (Jurnal Ilmiah Pendidikan dan Keislaman, 2022)
This study aims to empower peer tutors in the learning of high school students to see the effectiveness of improving student learning outcomes in history subjects. The method used is the Class Action Research (PTK) method. The research was conducted on class XI social studies 3 students at SMAN 1 Karangnunggal. Data collection was carried out using tests on each lesson to determine the improvement of student learning outcomes. The results showed an increase in student learning outcomes after participating in learning by empowering peer tutors. From the results of observations, it can be seen that overall the average student learning outcome has increased. Before empowering peer tutors the average student learning outcome was only 61.5, while after empowering peer tutors it increased to 67.3 in cycle I, and increased again to 77.6 in cycle II. It was concluded that the empowerment of peer tutors can improve the learning outcomes of high school students in history subjects